Comparison of Remote and Face-to-Face Ruqyah on Stress Levels Patients - Munawaroh, Fasikhatun; Kamal, Muhamad Ali Mustofa; Alviana, Fifi (An Idea Health Journal, 2025)
This study's objective is to compare the effectiveness of remote and face-to-face ruqyah on patient stress levels at Ruqyah Nurul Barokah. The quasiexperimental study design employed a two-group pretest-posttest design, and the instrument utilized was the Perceived Stress Scale 10 (PSS-10) questionnaire. The population studied comprised all patients of Ruqyah Nurul Barokah, with the research sample consisting of patients who experienced stress. A comprehensive data analysis was conducted using various statistical tests, including normality, homogeneity, Mann-Whitney U, and Wilcoxon tests. These tests were employed to ascertain the statistical significance of the two distinct ruqyah methods. The study revealed a substantial discrepancy between the pretest and posttest outcomes. Specifically, the Mann-Whitney U test yielded a Z value of -4,495, with a p-value of 0.000, indicating a statistically significant difference. A subsequent comparison between remote and face-toface ruqyah on stress levels yielded Z values of -3.413 and -3.414, respectively, with a p-value of 0.001. This finding indicates that face-to-face ruqyah had a more significant impact than remote ruqyah.